2021
DOI: 10.1038/s41598-021-89057-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effects of blending PODEn on performance, combustion and emission characteristics of heavy-duty diesel engines meeting China VI emission standard

Abstract: To study the influence of diesel fuel blended with polyoxymethylene dimethyl ethers (PODEn), a new alternative fuel with a high oxygen content and large cetane number, on the combustion characteristics, fuel economies, and emission characteristics of heavy-duty diesel engines that meet China VI emission standards, relevant tests were conducted on a supercharged intercooled high-pressure common-rail diesel engine. The PODEn were blended with diesel fuel at three different ratios (volume fractions of 10%, 20%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Another work [15] showed that under the speed of 2400 rpm and a full load condition, the smoke emissions of P10 (90 vol% diesel and 10 vol% PODE n ), P20, and P30 (70 vol% diesel and 30 vol% PODE n ) decreased by 29.7%, 67.8%, and 82.4%, respectively, in comparison with diesel fuel. The consistent trends that PODE n addition effectively reduced soot and PM emissions can be widely seen in [16][17][18]. In addition, adding PODE n also significantly decreased the total particulate number concentrations (PNCs) as expected.…”
Section: Introductionsupporting
confidence: 64%
“…Another work [15] showed that under the speed of 2400 rpm and a full load condition, the smoke emissions of P10 (90 vol% diesel and 10 vol% PODE n ), P20, and P30 (70 vol% diesel and 30 vol% PODE n ) decreased by 29.7%, 67.8%, and 82.4%, respectively, in comparison with diesel fuel. The consistent trends that PODE n addition effectively reduced soot and PM emissions can be widely seen in [16][17][18]. In addition, adding PODE n also significantly decreased the total particulate number concentrations (PNCs) as expected.…”
Section: Introductionsupporting
confidence: 64%
“…High concentration particulate matter (PM) in the air has always been one of the serious threats to human health and ecological environment (Zhang et al 2016a ) (Wang et al 2020a ). With the deepening of globalization, the proportion of transportation industry in PM emission is increasing (Zhao et al 2021 ) (Zhao et al 2019a ). Although influenced by the trend of future transportation energy reform (electrification and hybrid), the diesel engines still occupy a considerable part of the market share by virtue of fuel economy, operation reliability and high stability (Zhao et al 2018 ) (Zhang et al 2022e ) (Cai and Zhao 2022b ) (Ji et al 2014 ) (Cai and Zhao 2022e ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it is possible that due to higher combustion temperature promoted by common rail fuel injection coupled with a turbocharged induction air intake system, micro explosion of minute water particles in B30E emulsions could not effectively reduce combustion temperature in a magnitude observed in previous studies. These assertions were substantiated in a separate study which documented that a common rail turbocharged engine fueled with polyoxymethylene dimethyl ethers-diesel, a highly oxygenated fuel, was unable to effectively suppress NO x formation under various engine loads 50 .
Figure 7 NO x emission of test fuels at different engine loads.
…”
Section: Resultsmentioning
confidence: 92%